PARTICULARIZED CONVERSATIONAL IMMPLICATURE IN STAND-UP COMEDY SHOW BY ANTHONY JESELNIK: FIRE IN THE MATERNITY WARD - Abdan Ahadiyat (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2023)
Stand-up comedy and other forms of humor rely significantly on language and the use of words to amuse their audiences. To make humor more subtly funny, comedians frequently use a range of linguistic techniques, such as conversational implicature. This study investigates the phenomenon of the flouting maxims that raised the particularized conversational implicature in the Netflix stand-up comedy special